Understandable statistics : concepts and methods - Brase, Charles Henry; Brase, Corrinne Pellillo (Boston : Houghton Mifflin, 1999)
This book is about: Organizing data; Averages and variation; Elementary probability theory; The binomal probability distribution and related topics; ...
Keywords: Mathemetics; Mathematical statistics; Mathematical statistics